Personality traits or emotional dysregulation: a multiple mediation analyses of adolescent depression - Tore Aune; Leo Wolmer; Sigrid Flatås Aune; Daniel Hamiel; Hans M. Nordahl (Borderline Personality Disorder and Emotion Dysregulation)
Abstract Background In a similar way to depression, the development of borderline personality traits seems closely linked to the experience of Stressful Life Events (SLEs). This study examined the extent to which emotion regulation and personality traits simultaneously mediate and significantly attenuate the direct path between SLEs and depressive symptoms. Method Parallel and serial multiple mediation models were employed to analyze a sample of 196 adolescents assessed twice over a 12-month period. A regression-based path analysis approach was employed to simultaneously estimate the specific indirect effects of emotion regulation and borderline traits on the direct relationship between SLEs and depression. Results In a parallel multiple mediation model, both borderline traits and emotion regulation fully mediated the direct relationship between SLEs and depressive symptoms. The serial multiple mediation model also showed complete mediation. In this model, the indirect pathway from SLEs to depressive symptoms, first through borderline traits and subsequently through emotion regulation, accounted for 70.8% of the total indirect effect. In contrast, the indirect effects via borderline traits and emotion regulation accounted for 24% and 5.3% of the total indirect effects, respectively. Conclusion To strengthen clinical practice, early identification of borderline personality traits combined with targeted interventions to address specific symptoms may enhance emotional regulation and reduce the risk of depressive symptoms in vulnerable adolescents.